Think on your feet : tips and tricks to improve your impromptu communication skills on the job - Brown, Jen Oleniczak (Business professional collection, 2020)
"Develop the confidence and poise needed to take your communication skills to the next level Preparing for a presentation, interview, or salary negotiation can instill a sense of dread and fear in many people. Part of the fear comes from the risk of being caught off-guard and having to improvise on the spot. This is where the tools associated with improv come into play. While improv is traditionally associated with acting, it can also be a useful tool for effective workplace communication. Improv by definition forces us to be put on the spot, so we can practice our fear and work on our soft workplace skills. Drawing from cognitive and social psychology, behavioral economics, and actual improv activities, Think on Your Feet offers a fresh approach designed to increase your confidence and communication skills. Packed with expert advice and engaging exercises, the book teaches you how speak and act with confidence in any situation. You'll learn how to: Identify and bring out your best style for every type of professional communication Hone your focus and develop more effective active listening, interpretation, and nonverbal skills Handle uncomfortable situations, such as negotiating a raise, resigning, and resolving conflict Become a more effective communicator in both your professional and personal life"--